PENGARUH BUDAYA KERJA DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT ARTA BOGA CEMERLANG KOTA BENGKULU - Subandrio Subandrio; Dyna Avila (Yayasan Insani Mandiri Santani, 2022)
English translation. The purpose of this study was to determine the effect of work culture and work spirit on employee performance at PT Artaboga Cemerlang, Bengkulu City. This study uses quantitative methods and data collection by means of observation, interviews and questionnaires. The population in this study were all employees of PT Artaboga Cemerlang Bengkulu City, amounting to 60 people and sampling using the saturated sampling method. Based on the results of multiple linear regression, the regression equation form Y = 6.839 + 0.561 (X1) + 0.331 (X2). This equation can be explained by the influence of each independent variable, namely work culture (X1) and work spirit (X2) on employee performance (Y). And the coefficient of determination is R2 = 0.624 or 62.4%. Through hypothesis testing together (simultaneously) and individually (partial). In this study using the t test and f test. Work Culture (X1) and work spirit (X2) = 0.000, which means the Fsig value <0.05 indicates that together these variables have a positive and significant impact on employee performance. Keywords: Work Culture, Work Spirit, Employee Performance.